HUBUNGAN PENGETAHUAN, ASUPAN LEMAK, NATRIUM, KALIUM, SERAT DAN AKTIVITAS FISIK DENGAN KEJADIAN HIPERTENSI PADA ORANG DEWASA DI WILAYAH KERJA PUSKESMAS SUNGAI NANAM - Maria Nova; Hendra Mukhlis; Yaumil Daasnita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Riskesdas data shows that number of hypertension in West Sumatra Province is about 25.16% that is 12,650. The purpose of the study was to determine the relationship between knowledge of fat Intake, sodium, potassium, fiber and physical activity with the incidence of adults hypertension in Sungai Nanam Community Health Center. This type of research is a quantitative and cross sectional design. The location of this study is in Sungai Nanam Community Health Center. Sample of research was 77 adults aged 20-44 years, with chi-square tests. The results of the study were 54.5% of respondents suffering from hypertension, 37.7% of respondents had low knowledge levels, 70.1% of respondents consumed risky fats, 66.2% of respondents consumed sodium at risk, 94.8% of respondents consumed less potassium, 98.7% of respondents consumed fiber not as recommended, 35.1% of respondents had less activity. There was a relationship between the level of knowledge with the incidence of hypertension (P = 0.027), fat intake to the incidence of hypertension (P = 0.003), sodium intake with the incidence of hypertension (P = 0.001), and physical activity with the incidence of hypertension (P = 0.043), there was no relationship between potassium intake and the incidence of hypertension (P = 0.174) and fiber intake with the incidence of hypertension (P = 1,000). It is recommended for adults aged 20-44 years to consume less food that can increase blood pressure such as salted fish, salted eggs.